Artificial Intelligence (AI) and the Future of the Accounting Profession: Challenges and Opportunities (REMUNOM, 2025)
This article addresses the impacts of artificial intelligence (ai) on the accounting profession, highlighting the importance of accounting professionals adapting to these innovations, and the main challenges and opportunities that this technology brings. The main objective is to analyze how ai is transforming accounting routines, mainly through the automation of repetitive tasks, the analysis of large volumes of data, and the support for strategic decision-making. This article is justified by the need to understand how accounting professionals are dealing with this digital scenario and all these technological advances. The research adopts a qualitative approach, based on a bibliographic and documentary review, investigating the main ai tools used in accounting – such as machine learning, RPA, ORC, and business intelligence – and their practical effects on the daily lives of accountants. The risks associated with the adoption of AI are also discussed, such as data security, ethics in the use of technology, and the challenges of professional training. It is concluded that AI technologies in accounting have not negatively impacted the activities of professionals, on the contrary, they have brought about major changes in their routine activities, enabling everyone to be seen in a different way, with more productivity and responsibility, which are required by the professional environment.